2004
DOI: 10.1530/eje.0.1500579
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of leptin gene expression in different adipose tissues in children and adults

Abstract: Objective: Adipose tissue displays depot-specific metabolic properties and a predominant gene expression of leptin in subcutaneous tissue. The aim of the study was to evaluate leptin mRNA expression in various adipose tissues and to relate it to plasma leptin concentrations. Furthermore, developmental changes in leptin gene expression from childhood to adulthood were examined. Design and methods: Thoracic subcutaneous and intrathoracic adipose tissue specimens were obtained in 22 adults (51-81 years) and 23 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
5
18
0
Order By: Relevance
“…Many previous studies focusing on the importance of sc fat have examined older populations comprised of both males and females, and many include morbidly obese patients, who likely have greater than the normal complement of adipose tissue both visceral and subcutaneous, or those who have polycystic ovary syndrome and are anovulatory [10,[16][17][18][19][20][21]. Our study is unique in that it highlights a population (ovulatory women without insulin resistance) that has not been prior studied.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies focusing on the importance of sc fat have examined older populations comprised of both males and females, and many include morbidly obese patients, who likely have greater than the normal complement of adipose tissue both visceral and subcutaneous, or those who have polycystic ovary syndrome and are anovulatory [10,[16][17][18][19][20][21]. Our study is unique in that it highlights a population (ovulatory women without insulin resistance) that has not been prior studied.…”
Section: Discussionmentioning
confidence: 99%
“…FHL1 is involved in myocyte differentiation, and we speculate that it may have a similar role in adipocyte differentiation [4] and could serve as a potential marker for adipocyte differentiation or maturation as it is highly expressed in adipocytes and not in preadipocytes (van Beek et al, unpublished results). Leptin, previously described as a gene that is differentially expressed between adipose depots [24,50], was expressed at background levels, and was therefore, not included in the analysis. Furthermore, visfatin, also recently discovered as being differentially expressed between adipose depots [5], was not present on the microarray, and therefore was also not included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In studies primarily performed on adipose tissue of extreme obese individuals using several different techniques, including microarray technology [18,46,57], representational display analysis [40] and quantitative polymerase chain reaction (PCR) [14,24,43], Leptin [14,24,43,50,57], calcyclin, adipsin [40,63] and perilipin [2] were shown to be more highly expressed in the subcutaneous depot, while thrombospondin and carboxypeptidase E [46] were found to be more highly expressed in the omental depot. This confirmed the existence of functional differences between different depots.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, methylation in adipocytes influences LEP expression in vitro (7,12). However, measurements of LEP mRNA have revealed that especially in children LEP is differentially expressed depending on the adipose region (34).…”
Section: Early Life Environment and Lep Methylationmentioning
confidence: 99%